Faktor Penyebab Meningkatnya Pekerja Migran Indonesia (PMI) Di Korea Selatan Tahun 2017 - 2018 - Putri, Defi Ratna; Hartati, Anna Yulia (Kajian Hubungan Internasional, 2022)
International migration is one of the impacts of globalization which affects the phenomenon of sending Indonesian Migrant Workers. The amount of interest of the people who want to work abroad. It has a positive impact on the country, namely reducing the number of unemployed people, but from the other side it can also have negative impacts such as the risk of possible inhuman treatment of PMI. Thus, it is necessary to have a firm and pro-PMI protection policy. In this study, the authors used an explanative research method using a liberalism paradigm approach to determine the extent to which the role of negotiations could influence the regime so as to create policies that could change the mindset of better labor protection. This includes inclusiveness (internal) and exclusiveness (external) factors in making PMI protection policies in South Korea using the G to G program with the EPS system, where the government plays a direct role in the process of sending PMI without interfering with the private sector.